Assessing SWOT's Hydraulic Visibility on the Rhine: Precision Flow Lines and Slope‐Based Flood Wave Propagation Signatures - T. Ledauphin; P.‐A. Garambois; K. Larnier; M. Azzoni; C. Emery; N. Picot; S. Amzil; R. Fjørtoft; J. Maxant; H. Yésou (Earth and Space Science, 2025)
Abstract This study confirms the high accuracy of SWOT in capturing river surface elevations, slopes and hydraulic dynamics over the Franco‐German Rhine, exceeding expectations. By leveraging in situ networks, we evaluate SWOT products from pixel cloud (PIXC) to reach‐averaged measurements, demonstrating their effectiveness in mapping river surface topography and detecting key hydraulic signatures. The 1‐day Cal/Val data analysis successfully observed flood wave propagation, intumescence, and a rarely observed submersion wave positive slope, underscoring SWOT's value for river hydrology. Limitations in Reach and Node products from SWORD (Surface Water and Ocean Topography River Database), versions 14–16 were addressed by developing an improved SWORD model aligned with the Rhine's morphology, now integrated into SWORD v17. Using the RiverObs algorithm, all river products were reprocessed over the entire Cal/Val period (103 cycles), achieving a 1‐sigma absolute error of 12 cm at the node scale and 10 cm at the reach scale. SWOT data also revealed temporal river profile variations, capturing slope changes, flow waves, riffles, pools, alluvial deposits, and recharge zones. Future work will refine SWOT accuracy assessments, hydraulic denoising and slope computation, with nominal science orbit data and extend studies to narrower rivers (30–60 m width). Additionally, comparisons with high‐resolution lidar topo‐bathymetric DEMs and annual SWOT WSE profiles will advance understanding of how riverbed topography influences WSE. The demonstrated accuracy and spatial coverage of SWOT‐derived WSE and slope data highlight their potential for calibrating hydraulic models and supporting operational water management and hydraulic infrastructure planning.